Pengaruh Pemberian Bokashi Terhadap Pertumbuhan Vegetatif Dan Produksi Rumput Gajah (Pennisetum purpureum) - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2013)
The aim of this research were to know the effect of bokashi that giving the best result to growth vegetative and production elephant grass (Pennisetum purpureum). This research was designed by using Completely Random Design with single factor experiment thas is doses of bokashi (B), with the level of each doses, b0 = control (without bokashi), b1 = 10 ton ha -1, b2 = 20 ton ha -1 and b3 = 30 ton ha -1. The result showed that the applications bokashi giving the influences to the vegetative growth and production of elephant grass. Bokashi 30 ton ha-1 give the highest vegetative growth and production elephant grass.